European and Russian physician awareness of best management approaches for infections due to antibiotic-resistant Gram-negative bacteria. (3rd August 2017) - Irani, Paurus; Salimi, Tehseen; Epstein, Robert; Leone-Perkins, Megan; Aubert, Ronald; Khalid, Mona; Epstein, Emma; Teagarden, J. Russell
Abstract: Objectives: The rapid spread of infections due to antibiotic-resistant, Gram-negative bacteria in Europe and surrounding regions requires a heightened level of awareness among physicians within their practice settings. Methods: We surveyed 800 physicians who treat these infections across France, Germany, Spain, Italy, and Russia to assess their awareness of best management approaches. Results: We found that more than two-thirds do not consider themselves highly aware of best management practices. The respondents are facing these resistant infections as evidenced by the antibiotics they report using and their stated interest in newer agents. Respondents indicated that precious time is lost waiting for culture results, but also said they will need more information about accuracy, use, and costs for adopting rapid molecular testing. Conclusions: The survey further identified the need for treatment guidelines and clinical decision support tools that can be applied at the bedside.